Kepatuhan Penggunaan Alat Pelindung Diri pada Pekerja Proyek Pengendalian Banjir Sunga Bekasi dan Faktor yang Mempengaruhinya - Septiyani, Dian; Sangadji, Namira Wadjir; Handayani, Putri; Muda, Cut Alia Keumala (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Abstract Background: Based on preliminary observations made by researchers to 10 workers of the Bekasi River flood control project package 1, 8 workers did not comply with ppe in accordance with company standards. The purpose of this study was to determine the factors related to compliance with the use of Personal Protective Equipment (PPE). Method: This study had a sample of 88 people with total sampling technique, using quantitative method with cross sectional design. This study used the primary data collection method obtained through interviews and observations using checklist sheets and secondary data obtained from company documents in the form of company descriptions, company procedures and labor lists. Results: There is a relationship between knowledge and compliance of PPE use (P Value 0.013 and PR = 2.461), there is a relationship between ppe use attitudes and compliance (P Value 0.000 and PR = 0.419) and there is a relationship between supervision and compliance of PPE use (P Value 0.000 and PR = 0.432). Conclusion: Knowledge, attitude and supervision are factors related to the compliance of the use of PPE in workers of the Bekasi River Flood Control Project Package 1. It is recommended to ensure that educational programs run, evaluate employment contracts with foremen and subcontractors and provide strict sanctions to workers who do not comply with the use of PPE. Keywords: construction, compliance, PPE, knowledge, attitude, supervision